High-Definition Chromoendoscopy Improves Dysplasia Detection in Ulcerative Colitis - Lederman, Lynne (MD Conference Express, 2015)
A small single-center trial showed that high-definition chromoendoscopy improves detection of dysplastic lesions in patients with long-standing ulcerative colitis during screening endoscopy as compared with high-definition white light endoscopy. These results will be confirmed in a larger UK study enrolling 1600 patients.